Pelatihan Kepemimpinan Bidang Ketrampilan Public Speaking dan Penyusunan Program Kerja Kebidelan Seminari Palembang T.A. 2017/2018 - Clara, Catharina; Inharjanto, Anselmus; Ratnaningsih, Paskalina Widiastuti; Leovani, Ega; Irzawati, Ira (Prosiding University Research Colloquium, 2018)
Student organization is part of the formation at St. Paul’s Minor Seminary in Palembang, South Sumatra. Seminary’s new student organization committee has been assigned with various tasks related to the vision of 4Ss (i.e. Sanctitas or Sanctity, Sanitas or Health, Scientia or Science, and Socialitas or Communal Life). The aim of this leadership training of public speaking skills and work programme planning for internal student organization of St. Paul Minor Seminary, Palembang in academic year 2017/2018 is to increase leadership ability of Seminary students (or seminarians) especially in selfmanagement and as internal student organisation committee both public speaking and work programme planning. The methods used were lecture and group practice. This activity was conducted in two days. The first day activities were discussing basic leadership management and public speaking continued with group practice. The second day activity was introduction to work program planning continued with real practice in groups. The analysis result of questionnaire reveals that the respondents’ opinions dealing with training activities in leadership, self-management, public speaking, and work programme planning demonstrate that the average score is in the agree and strongly agree scales. This fact indicates that the activity is beneficial for the seminarians. It facilitates the seminarians to improve their abilities related to leadership, public speaking and work programme planning.